2023
DOI: 10.3390/ijms242216259
|View full text |Cite
|
Sign up to set email alerts
|

Potential Implications of miRNAs in the Pathogenesis, Diagnosis, and Therapeutics of Alzheimer’s Disease

Long Wang,
Xindong Shui,
Yuelin Diao
et al.

Abstract: Alzheimer’s disease (AD) is a complex multifactorial disorder that poses a substantial burden on patients, caregivers, and society. Considering the increased aging population and life expectancy, the incidence of AD will continue to rise in the following decades. However, the molecular pathogenesis of AD remains controversial, superior blood-based biomarker candidates for early diagnosis are still lacking, and effective therapeutics to halt or slow disease progression are urgently needed. As powerful genetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 248 publications
0
5
0
Order By: Relevance
“…This alteration has a notable effect on the development of various neurodegenerative diseases such as Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), and amyotrophic lateral sclerosis (ALS) [36]. In AD, miRNAs in serum, cerebrospinal fluid, and brain tissue, as well as in transgenic models, have been studied [37][38][39][40][41]. Few studies have reported miRNAs in the early stages or related to the progression of AD [22,[41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…This alteration has a notable effect on the development of various neurodegenerative diseases such as Alzheimer's disease (AD), Parkinson's disease (PD), Huntington's disease (HD), and amyotrophic lateral sclerosis (ALS) [36]. In AD, miRNAs in serum, cerebrospinal fluid, and brain tissue, as well as in transgenic models, have been studied [37][38][39][40][41]. Few studies have reported miRNAs in the early stages or related to the progression of AD [22,[41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…67 Muscleblind-like (MBNL) proteins are involved in developmental splicing and could potentially influence MAPT splicing, although direct evidence remains sparse. 68,69 71,72 ).…”
Section: F I G U R Ementioning
confidence: 99%
“…These miRNAs can indirectly regulate the expression of exon 10 trans ‐acting factors, thereby affecting the balance between 3R and 4R TAU isoforms. While the specific mechanisms by which these miRNAs regulate MAPT alternative splicing are still being elucidated, it is clear that miRNAs play a significant role in modulating the splicing of TAU pre‐mRNA, particularly in the context of tauopathies (reviewed in 71 , 72 ).…”
Section: Mapt Alternative Splicing and Tau Isoformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the miRBase database ( ; accessed in 1 December 2023) lists over 2588 distinct miRNAs that are involved in nearly every cellular process, highlighting the vast and complex nature of this field of study [ 7 , 8 ]. Moreover, alterations in miRNA expression have been implicated in a myriad of diseases, emphasizing their importance in maintaining cellular homeostasis [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%